Urban Chagas disease in children and women in primary care centres in Buenos Aires, Argentina - Moscatelli, Guillermo (2015)
The primary objective of this study was to estimate the prevalence of this disease in women of childbearing age and children treated at health centres in underserviced areas of the city of Buenos Aires. Demographic and Chagas disease status data were collected. Samples for Chagas disease serology were obtained on filter paper and the reactive results were confirmed with conventional samples. A total of 1,786 subjects were screened and 73 positive screening results were obtained: 17 were from children and 56 were from women. The Trypanosoma cruzi infection risk was greater in those individuals who had relatives with Chagas disease, who remember seeing kissing bugs, who were of Bolivian nationality or were born in the Argentine province of Santiago del Estero. The overall prevalence of Chagas disease was 4.08%. Due to migration, Chagas disease is currently predominantly urban. The observed prevalence requires health programme activities that are aimed at urban children and their mothers. Most children were infected congenitally, which reinforces the need for Chagas disease screening of all pregnant women and their babies in Argentina. The active search for new cases is important because the appropriate treatment in children has a high cure rate.